1992
DOI: 10.1002/cm.970220308
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional motility cycle in leukocytes

Abstract: A 3-dimensional dynamic image analyzing system (3D-DIAS) has been developed in which a translocating cell is optically sectioned in the z-axis within a 2 sec period; the perimeter of the cell in each section is digitized into the 3D-DIAS data file, and the digitized perimeters are wrapped in order to reconstruct the cell image in three dimensions. Using 3D-DIAS, we have obtained the first dynamic 3-dimensional description of human polymorphonuclear leukocytes (PMN) translocating on a glass surface. A general b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…Dictyostelium cells are similar to leukocytes, in that they are fast-moving cells with an irregular shape (Murray et al, 1992;Wessels et al, 1994). Talin (Kreitmeier et al, 1995) and alphaactinin (Brier et al, 1983) have been identified as adhesionrelated proteins and their subcellular localization is similar to that of actin.…”
mentioning
confidence: 91%
“…Dictyostelium cells are similar to leukocytes, in that they are fast-moving cells with an irregular shape (Murray et al, 1992;Wessels et al, 1994). Talin (Kreitmeier et al, 1995) and alphaactinin (Brier et al, 1983) have been identified as adhesionrelated proteins and their subcellular localization is similar to that of actin.…”
mentioning
confidence: 91%
“…An example of switching migration strategy has been reported in the case of tumor cells, which can convert from a mesenchymal to an amoeboid motility mode following metalloproteinase inhibition (9,10). In addition, studies in the amoeba Dictyostelium (11) and in neutrophils (12) have suggested the possibility of motility kinetics with discontinuous adhesion characteristics, but the causes and molecular details remain unknown. Given the number of T cell functions that rely on migration to specific tissues and interaction with other cells (8,13), we sought to examine the general principles of motility in lymphocytes, particularly in relation to substrate adhesion and motility modes.…”
mentioning
confidence: 99%
“…The 4D description of the basic motile behavior of D. discoideum amoebae presented here provides a contextual framework for developing models of motility, interpreting behavioral defects of mutants, deducing the roles cytoskeletal and regulatory molecules play in motility, and determining how chemotactic gradients manipulate basic motile behavior. Studies are now in progress to test which of the characteristics of D. discoideum motility hold true for other cell types, most notably human polymorphonuclear leukocytes (48,66), and how they are manipulated by spatial and temporal gradients of the chemoattractant cyclic AMP (63).…”
Section: Discussionmentioning
confidence: 99%